2020
DOI: 10.1002/qua.26511
|View full text |Cite
|
Sign up to set email alerts
|

On the study of influence of molecular arrangements and dipole moment on exciton binding energy in solid state

Abstract: Exciton binding energy (Eb) is one of the key factors affecting charge transfer and charge separation in organic solar cells (OSCs). However, most studies on Eb only focus on a single molecule, which is far from the real situation. How molecular arrangements and dipole moment influence Eb in solid state is still an open question. In the present work, a methodology combining the polarizable continuum model with calculated static dielectric constants, optimally tuned long‐range corrected hybrid density functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Thus, the molecular packing will affect the E b of organic materials. [ 61 ] For example, Zheng et al [ 62 ] calculated the E b values of the single molecule and dimer of subphthalocyanine chloride (SubPc) ( Figure ) and found that dimer s 3 packing state of SubPc had the smallest E b . Wei et al [ 56 ] reported that the 3D packing crystal of the OSCs could effectively reduce E b with an extremely weak E b of 0.04 eV calculated in 4TIC (Figure 8).…”
Section: Effect Of the Molecular Packing On E Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the molecular packing will affect the E b of organic materials. [ 61 ] For example, Zheng et al [ 62 ] calculated the E b values of the single molecule and dimer of subphthalocyanine chloride (SubPc) ( Figure ) and found that dimer s 3 packing state of SubPc had the smallest E b . Wei et al [ 56 ] reported that the 3D packing crystal of the OSCs could effectively reduce E b with an extremely weak E b of 0.04 eV calculated in 4TIC (Figure 8).…”
Section: Effect Of the Molecular Packing On E Bmentioning
confidence: 99%
“…Thus, the molecular packing will affect the E b of organic materials. [61] For example, Zheng et al [62] Figure 7. a) ϵ r versus frequency of Y6 and Y6-4O, and b) the recently reported OSCs based on high-dielectric-constant organic semiconductors.…”
Section: Effect Of the Molecular Packing On E Bmentioning
confidence: 99%
“…Exciton binding energy is a key factor in influencing charge transfer and separation. The following equations were used to calculate exciton binding energy with IEF-PCM [49,50]:…”
Section: Methodsmentioning
confidence: 99%
“…With the unremit-ting efforts of Zhan Xiaowei's group, 2,2'-[ [6,6,12,12-tetrakis (4-hexylphenyl)-s-indacenodithieno[3,2-b]thiophene]methylidyne(3-oxo-1H-indene-2,1(3H)-diylidene)]]bis(propanedinitrile) (ITIC) and 2,2'-2,2'-[(4,4,9,9-tetrahexyl-4,9-dihydro-s-indaceno[1,2-b:5,6-b']dithiophene-2,7-diyl)bis[methylidyne(3oxo-1H-indene-2,1(3H)-diylidene)]]bis[propanedinitrile] (IDIC) (Fig. 1(b)) were reported in 2015 and 2017 respectively, which opened a new chapter in the research of PSCs [14,18] . A series of works have been reported, and the related research results are greatly conducive to the in-depth understanding of PSCs, thus promoting the rapid development of industrial research.…”
Section: Introductionmentioning
confidence: 90%